Reshaping the European Union Landscape: The Rise of Far-Right Movements and Their Potential Impact on Middle East Policy - Zaoui Rabah (İmgelem)
The rise of far-right parties within the European Union has raised significant concerns about potential shifts in EU foreign policy, particularly with regard to the Middle East. This development challenges the core values of the EU and has the potential to markedly reshape its diplomatic strategies, aid distribution, and regional engagement. This analysis examines key areas of Middle East policy likely to be influenced by the growing presence of far-right parties in EU institutions, including immigration and refugee policies, the EU's stance on the Israeli-Palestinian conflict, relations with Iran, and involvement in peace processes in the region. Additionally, the study emphasizes potential shifts in power dynamics within EU decision-making bodies concerning Middle East policy, underscoring the urgency of the issue. The hypotheses suggest that the increased influence of far-right parties may result in more restrictive immigration policies, stronger pro-Israel positions, a more confrontational approach towards Iran, diminished EU involvement in Middle East peace initiatives, and a reduction in regional financial aid. The research also explores the likelihood of greater bilateral engagement between individual EU member states and Middle Eastern countries, which could weaken the EU's common foreign policy and lead to a more fragmented regional strategy. This study highlights the critical importance of understanding the complexities of this phenomenon, as the mainstreaming of far-right ideologies has profound implications for European politics and the EU’s role in the Middle East. Addressing these challenges is essential for safeguarding the EU’s foundational values and maintaining its ability to navigate intricate geopolitical landscapes.